Analysis of head impacts during sub-elite hurling practice sessions. Issue 11 (3rd June 2018) - O'Sullivan, D.; Roe, M.; Blake, C.
ABSTRACT: The reported incidence of head and neck injuries in hurling is 0.12 per 1000 hours, but no previous research has quantified head impact characteristics in this sport. Here, a wireless accelerometer and gyroscope captured head impacts, in 20 senior club level hurling players. Peak linear and rotational acceleration and impact location were recorded during three hurling training sessions, each player participating once. A mean of 27.9 impacts (linear acceleration >10g) per player, per session were recorded; 1314 impacts during a total exposure time of 247 minutes. Only 2.6% impacts had peak linear acceleration of >70g and 6.2% had peak rotational acceleration >7900 rad/s 2 . There were significant differences in the number and magnitude of impacts, quantified by the accelerometer, between three training sessions of differing intensity (ŋ2 0.03–0.09, p < 0.001). This study represents a first step in quantifying head impacts during hurling, demonstrating the feasibility of this technology in the field. The sensors were able to discriminate between sessions of varying intensity. These data can be used to develop athlete monitoring protocols and may be useful in developing innovative helmet-testing standards for hurling. The potential for this technology to provide feedback has clinical utility for team medical personnel.